Variation in carbon isotope values among chimpanzee foods at Ngogo, Kibale National Park and Bwindi Impenetrable National Park, Uganda. Issue 10 (26th February 2016) - Carlson, Bryce A.; Crowley, Brooke E.
Abstract : Stable isotope values in primate tissues can be used to reconstruct diet in the absence of direct observation. However, in order to make dietary inferences, one must first establish isotopic variability for potential food sources. In this study we examine stable carbon isotope (δ 13 C) values for chimpanzee ( Pan troglodytes ) food resources from two Ugandan forests: Ngogo (Kibale National Park), and Bwindi Impenetrable National Park. Mean δ 13 C values for plant samples are equivalent at both sites. Plant δ 13 C values are best explained by a multivariate linear model including plant part (leaves, pith, flowers, and fruit), vertical position within the canopy (canopy vs. ground), and taxon ( R 2 = 0.6992). At both sites, leaves had the lowest δ 13 C values followed by pith and fruit. Canopy resources have comparable δ 13 C values at the two sites but ground resources have lower δ 13 C values at Ngogo than Bwindi (−30.7 vs. −28.6‰). Consequently, isotopic differences between ground and canopy resources (4.2 vs. 2.2‰), and among plant parts are more pronounced at Ngogo. These results demonstrate that underlying environmental differences between sites can produce variable δ 13 C signatures among primate food resources. In the absence of observation data or isotope values for local vegetation, caution must be taken when interpreting isotopic differences among geographically or temporally separated populations or species. Am. J. Primatol. 78:1031–1040, 2016. © 2016 Wiley Periodicals, Inc.